Influence of Cigarette Smoking on Osteonecrosis of the Femoral Head (ONFH): A Systematic Review and Meta-Analysis. Issue 5 (September 2017) - Wen, Zhenxing; Lin, Zan; Yan, Wenlong; Zhang, Jian
Background: Current studies demonstrate controversy regarding the relationship between cigarette smoking and osteonecrosis of the femoral head (ONFH). Methods: We conducted a meta-analysis to evaluate the association between smoking and ONFH. Relevant articles published before September 2016 were identified by a systematic search of EMBASE and MEDLINE via Ovid. Summary odds ratios (OR) were calculated using random effects models, and study quality was assessed using a modified Newcastle-Ottawa scale. Results: 102 citations were screened and 7 case-control studies were identified and included in the review. When compared with nonsmokers, current smokers had a higher risk of developing ONFH (OR 2.53; 95% confidence interval [CI] 1.68-3.79), as did former smokers (OR 1.82; 95% CI, 1.10-3.00). Within the group of current smokers, those classified as heavy smokers (with a daily number >20 cigarettes/day) demonstrated higher risks of ONFH (OR 2.03; 95% CI, 1.29-3.19), and light smokers classified as smoking <20 cigarettes/day, also demonstrated a higher risk of ONFH when compared with nonsmokers (OR 1.73; 95% CI, 1.06-2.83). When smoking was classified by pack-years, heavy smokers (>20 pack-years) were at a higher risk of ONFH (OR 2.26; 95% CI, 1.24-4.13), but no significant difference in risk was identified in light smokers (<20 pack-years) (OR 1.81; 95% CI, 0.88-3.71) when compared with nonsmokers. Conclusions: Our meta-analysis showed that current smokers were at a higher risk of ONFH, this high risk can also be found in former smokers. And heavy cigarette smoking showed a higher risk of ONFH than light smoking.